Controlling the polymorphism of carbamazepine-saccharin cocrystals formed during antisolvent cocrystallization using kinetic parameters - Lee, Min-Jeong; Wang, In-Chun; Kim, Min-Ju; Kim, Paul; Song, Keon-Hyoung; Chun, Nan-Hee; Park, Hwa-Gyoo; Choi, Guang Jin (The Korean journal of chemical engineering, 2015)
The cocrystal approach has been extensively investigated over the last decade as one of the most promising methods toward modifying the dissolution behavior of insoluble drug substances. This study demonstrates that the polymorphism of pharmaceutical cocrystalline powders prepared via antisolvent methods can be controlled using kinetic parameters. A carbamazepine-saccharin (CBZ-SAC) cocrystal was selected as a model drug in this study. This crystal was manufactured through a scaled-up antisolvent process with a total solution volume of 4.5 L. CBZ-SAC cocrystal crystalline powders were synthesized by adding 3 L of water as the antisolvent into 1.5 L of CBZ and SAC in methanol, whereby the antisolvent addition rate and the agitation speed were varied as the principal kinetic parameters. To investigate how cocrystallization proceeds under each condition, periodical sampling was combined with off-line characterization and in-line near-infrared (NIR) measurements to monitor the progress of reaction over the 120-minute process. We found that the creation of form-I was preferred when the addition speed or agitation speed was increased, but a highly pure form-II resulted if kinetic conditions were reversed. These differences in polymorphism can be explained by changes in kinetic characteristics when the process is monitored by NIR. This study is directly applicable to the industrial synthesis of these types of materials, precisely when specific CBZ-SAC cocrystalline polymorphs must be manufactured on a large scale.